PENGARUH SUCCESSION PLANNING DAN LEADERSHIP TERHADAP FAMILY BUSINESS SUSTAINABILITY - Salim, Stefanus; Effendy, Junko Alessandro (Universitas Ciputra Surabaya, 2023)
Family Business has great impact or contribution in a country’s economic sector. However, like business in general the family firm has its challenge. Succession plan for family firm is a thing that needs to be thought by family business’ owner to achieve firm sustainability to the next generation. However, this succession plan is also the challenge that has to be faced, because survival rate level from one generation to another generation is lower. The survival rate of first generation to the second generation is 30%, second generation to third generation is 12%, and third generation to fourth generation is 3%. This research is done to find out the effect of succession planning and leadership on family business sustainability. In order to collect the research data, the researcher distributes questionnaires to 74 respondents who are the member of ninth and tenth batch of Universitas Ciputra guild family business with Slovin formula and simple random sampling. This research uses multiple linear analysis test method with the help of SPSS (Statistical Product and Service Solutions)software. The test result in this research indicates that both variables of Succession Planning and Leadership have significant effect on Family Business Sustainability.Keyword: Succession Planning, Leadership, Family Business Sustainability